Sustainable investments in responsible SMEs: That's what's distinguish government VCs from private VCs - Jeaneth Johansson; Malin Malmström; Joakim Wincent (Journal of Risk and Financial Management, 2021)
Researchers question the impact of governmental venture capitalists (GVC) compared to private venture capitalists (PVC), but we know little about why this difference occurs and if this criticism is justified. We observed a group of GVCs and developed a new model that describes the way that GVCs process signals pre- and post-decisions. Certain macro level factors severely undermine micro level performance, causing GVCs to financially underperform with respect to PVCs. This helped us to understand that GVCs do not make investment decisions in the same way as PVCs, and what undermines the performance of GVCs' decision-making processes. The main goals of GVCs are to promote investments in responsible SMEs, mobilizing societal impact. We discuss that the criticism of GVC needs to be more nuanced, as they have a different role than PVC in the financial system as providers of sustainable investments in responsible SMEs.
Keywords: 330; sustainable investments; entrepreneurial finance; government venture capital; private venture capital; responsible ventures; decision-making